2021
DOI: 10.1002/2050-7038.12770
|View full text |Cite
|
Sign up to set email alerts
|

ANFIS model based on fuzzy C‐mean , grid partitioning and subtractive clustering to detection of stator winding inter‐turn fault for PM synchronous motor

Abstract: Summary In this paper, one‐of‐a‐kind hybrid intelligence models based on the adaptive neuro‐fuzzy inference system (ANFIS) the use of C‐mean fuzzy clustering (FCM), grid partitioning (GP), and subtractive clustering (SC) fashions are used. Three extraordinary gaining knowledge of algorithms that were incorporated with the ANFIS version are used to locate fault prevalence within the permanent magnet synchronous motor (PMSM). Due to the fact it may both stumble on any inconvenience with any force and is flexible… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…The line fault early warning model is mainly divided into seven links, such as information collection and data preprocessing [17]. The multi-source data algorithm is used to mine massive data, so as to obtain the occurrence index of fault factors of different fault types On this basis, using the feature items in the fault identification feature library and the time series data composed of time series data with standard time, the corresponding time series model is established, the time series spacing is set, the method and method of optimal diagnosis are determined, and the fault alarm is carried out for the transmission system that meets a certain critical point [18]. By filtering the data, it is found that some characteristics have a certain correlation with the fault.…”
Section: Measuring Equipmentmentioning
confidence: 99%
“…The line fault early warning model is mainly divided into seven links, such as information collection and data preprocessing [17]. The multi-source data algorithm is used to mine massive data, so as to obtain the occurrence index of fault factors of different fault types On this basis, using the feature items in the fault identification feature library and the time series data composed of time series data with standard time, the corresponding time series model is established, the time series spacing is set, the method and method of optimal diagnosis are determined, and the fault alarm is carried out for the transmission system that meets a certain critical point [18]. By filtering the data, it is found that some characteristics have a certain correlation with the fault.…”
Section: Measuring Equipmentmentioning
confidence: 99%
“…The input space can be divided appropriately, and the number of membership functions (MFs) and the parameters for each input domain can be reasonably determined [28]. There are two other well-known methods to construct fuzzy inference systems: (1) grid partitioning; (2) fuzzy c-means clustering [29]. It has been proven that SC is better than other algorithms [30,31], and it was adopted as the method to generate the fuzzy inference system in the ANFIS.…”
Section: The Sc-anfis Submodelmentioning
confidence: 99%
“…ANFIS is a hybrid of ANN and fuzzy logic that can incorporate important features of both techniques [13]. The ANN's learning ability and the fuzzy system's logical reasoning ability have been combined in ANFIS [14]. ANFIS takes into account the positive features of ANN and fuzzy logic techniques for classifying and detecting different rotating machinery faults [15].…”
Section: Introductionmentioning
confidence: 99%